Influence of Rhizobia and Endophytic Bacteria on Adaptation and Productivity of Glycine Max (L.) Merr. Under Hyperthermіa and Drought Conditions - Shevchuk, N.V.; Tytova, L.V.; Iutynska, G.O.; Sergiienko, V.G.; Katrii, V.B.; Шевчук, Н.В.; Титова, Л.В.; Іутинська, Г.О.; Сергієнко, В.Г.; Катрій, В.Б. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
In the context of global adverse climate change, the use of microorganisms to increase plant stress resistance is becoming increasingly important. In this aspect, the use of rhizobia and endophytic bacteria for legume protection to abiotic stresses is still poorly understood. The aim of the study was to investigate the modulating effect of pre-sowing endophyte-rhizobial seed inoculation on the level of antioxidant activity of leaves and roots, water regime, and productivity of soybeans under conditions of hyperthermia and drought, as well as the preservation of this beneficial effect on the physiological homeostasis in the next generation of plants. Methods. The following methods were used in the study: microbiological (cultivation of microorganisms to obtain microbial bioformulations), biochemical (determination of total antioxidant and catalase activities), physiological (determination of plant water balance), field (soybean plant cultivation, determination of their productivity), and statistical (the significance of the differences determination). The endophytic bacteria Bacillus sp.4 in composition with Bradyrhizobium japonicum UCM B-6018, B-6023 and B-6035, soybean plants of the Sculptor variety were used in the study. Results. The most negative impact of hydrothermal growing conditions was experienced by non-inoculated plants of the control variant, which was confirmed by high values of antioxidant activity − 32% for leaves and 55% for soybean roots, while in the case of endophytic-rhizobial inoculation, these values were lower by 12.5 and 5.5%, respectively. The level of catalase activity was the highest in the inoculated plants, which may indicate an active functioning of the enzyme antioxidant system. Inoculation improved the water regime of soybean plants. The values of water supply, humidity, and water-holding capacity of the leaves of inoculated plants were higher than those of control plants, which directly contributed to better adaptation to hydrothermal conditions. The positive effect of pre-sowing endophytic-rhizobial inoculation of seeds on plant stress resistance was confirmed by an increase in their productivity, in particular, an increase in yield per plant. Conclusions. The use of complex inoculants of soybean based on rhizobia and endophytic bacteria is promising for the creation of new adaptive biotechnologies capable of maintaining the physiological homeostasis of the phytopartner under adverse conditions, which will help prevent yield losses of this crop from abiotic stresses.